Training of Indonesian National Police Pilots to Improve Competence, Professionalism and Aviation Safety - Timonora, Stefanus; Ariyanto, Wahyu (KnE Social Sciences, 2022)
Training of police pilots is not currently carried out periodically and continuously, resulting in a lack of knowledge of the pilots, which has an impact on competence, professionalism and flight safety. This research aimed to understand the condition of the current training of the Indonesian National Police pilots, to understand obstacles and the forms of innovation needed to improve competence, professionalism and aviation safety. This was qualitative research with a case study approach. The key informants in this research were the Indonesian National Police Commander, flight instructors, active pilots, student pilots, the Director of the Indonesian Aviation Academy, Banyuwangi, and the Head of Garuda Indonesia Training Center. This study was conducted in the Professional Improvement Division, of the Marine and Air Police Corps, Security Maintenance Agency, Indonesian National Police. Data were collected through interviews conducted online. Further information and verification were obtained from key informants. We also used observations and document review. It was found that there were still some drawbacks in the implementation of education for the Indonesian National Police, according to a review of the eight education standards of the Indonesian National Police. These eight standards related to: graduates’ competence, content, process, educators and education staff, infrastructure, management, financing, and evaluation. The researchers also identified obstacles to implementing training innovations. Based on the results, it is recommended that the Professional Improvement Division should find breakthroughs or innovations in education and training for Indonesian National Police pilots to improve their competence, professionalism and aviation safety, especially to meet the needs of updated knowledge on aviation with easy access that can be learned anywhere and anytime. This corresponds to the sixteen priority programs of the Chief of Indonesian National Police, Pol. Gen. Listyo Sigit Prabowo, with two important points of emphasis: to have excellent Indonesian National Police human resources and modern police technology. Keywords: innovation, education and training, competence, professionalism, aviation safety